Differential gene expression patterns between the head and thorax of Gynaephora aureata are associated with high-altitude adaptation - Zhao, Jia-Rui; Hu, Shi-Yun; Zhang, Li-Jun; Zhang, Li; Yang, Xing-Zhuo; Yuan, Ming-Long (Frontiers in Genetics, 2023)
Grassland caterpillars (Lepidoptera: Erebidae: Gynaephora) are important pests in alpine meadows of the Qinghai-Tibetan Plateau (QTP). These pests have morphological, behavioral, and genetic adaptations for survival in high-altitude environments. However, mechanisms underlying high-altitude adaptation in QTP Gynaephora species remain largely unknown. Here, we performed a comparative analysis of the head and thorax transcriptomes of G. aureata to explore the genetic basis of high-altitude adaptation. We detected 8,736 significantly differentially expressed genes (sDEGs) between the head and thorax, including genes related to carbohydrate metabolism, lipid metabolism, epidermal proteins, and detoxification. These sDEGs were significantly enriched in 312 Gene Ontology terms and 16 KEGG pathways. We identified 73 pigment-associated genes, including 8 rhodopsin-associated genes, 19 ommochrome-associated genes, 1 pteridine-associated gene, 37 melanin-associated genes, and 12 heme-associated genes. These pigment-associated genes were related to the formation of the red head and black thorax of G. aureata. A key gene, yellow-h, in the melanin pathway was significantly upregulated in the thorax, suggesting that it is related to the formation of the black body and contributed to the adaptation of G. aureata to low temperatures and high ultraviolet radiation in the QTP. Another key gene, cardinal, in the ommochrome pathway was significantly upregulated in the head and may be related to red warning color formation. We also identified 107 olfactory-related genes in G. aureata, including genes encoding 29 odorant-binding proteins, 16 chemosensory proteins, 22 odorant receptor proteins, 14 ionotropic receptors, 12 gustatory receptors, 12 odorant degrading enzymes, and 2 sensory neuron membrane proteins. Diversification of olfactory-related genes may be associated with the feeding habits of G. aureata, including larvae dispersal and searching for plant resources available in the QTP. These results provide new insights into high-altitude adaptation of Gynaephora in the QTP and may contribute to the development of new control strategies for these pests.